Dynamics of a cavitation bubble near a solid surface and the induced damage. (January 2020) - Sagar, Hemant J.; el Moctar, Ould
Abstract: Numerical and experimental studies of the dynamics of a cavitating bubble near a resilient metal surface were performed. To augment the experimental flow visualizations of a collapsing bubble, numerical simulations were conducted to more thoroughly identify the collapse dynamics and analyze the flow. A bubble collapse was captured using a high-speed camera and back illumination. The metal sample was made of pure aluminum placed near a collapsing cavitation bubble at various distances from the metal surface. Width, depth, and volume of the induced material deformations were measured using an optical microscope and a three-dimensional profilometer and then compared against existing experimental data from the literature. The cavitating bubble's dynamics and the related flow were simulated numerically using the open source finite volume based flow solver CavitatingFOAM. This code solved the Navier–Stokes equations for compressible two-phase flows using an Euler–Euler approach, including the barotropic equations of state. Bubble shapes, collapse times, and obtained damage parameters were compared to experimental observations. Impact velocities, pressures, shear rates, and various flow phenomena were discussed, providing broad insight into bubble dynamics and the induced damage.